Comparison in the effects of alumina, ceria and silica nanoparticle additives on the combustion and emission characteristics of a modern methanol-diesel dual-fuel CI engine. (15th June 2021) - Wei, Jiangjun; He, Chengjun; Fan, Chenyang; Pan, Suozhu; Wei, Mingliang; Wang, Chenfang
Highlights: Nanoparticle (NP) addition improves methanol-diesel fuel (MDF) ignition at <30% load. Alumina and ceria nanoparticles cause stronger ignition improvement of MDF than silica. NP addition in MDF increases peak cylinder pressure by ≤4.6% in 100 ppm dosage. NP addition exerts negatively effects on reduction of CO, HC and smoke emissions for MDF. Alumina and ceria nanoparticle cause higher NOx deterioration degrees than silica. Abstract: Methanol is widely used as a potential alternative source for diesel fuel and can reduce the CO, THC and smoke emissions of the CI engines. However, the lower cetane number and energy content of methanol hinder the high substitution of methanol over diesel fuel. Introducing nanoparticles as fuel-additive is an effective approach to cope with this issue. In the present work, the alumina, ceria and silica nanoparticles were separately mixed into methanol in mass proportions of 25, 50 and 100 ppm with the composite surfactant of sodium dodecyl benzene sulfonate and cetyl trimethyl ammonium bromide (1:1 mass fraction) to create the nanofluid. The nanofluid was then injected into the intake port to combust synergistically with the mineral diesel fuel injected by the other high-pressure injection system, generating the nanoparticle-assisted methanol-diesel fuel mode (NMF). The characteristics of combustion and pollutant emission of NMFs were investigated with 10%, 30% and 50% methanol substituted level (M10, M30 and M50, respectively), at 10–90% engine loads of a constant engine speed. The results showed that the substitution of methanol led to an extension in the ignition delay but a shortening of combustion duration than diesel fuel. The additional introduction of alumina and ceria nanoparticles in each dosage, and silica nanoparticles in 100 ppm dosage, into M10 slightly shortened the ignition delay at 10% load conditions. When dosed into M50 fuel, all the three nanoparticles in various dosages led to shortened ignition delay at 10–50% engine loads. Over the test conditions, the addition of nanoparticles all caused a distinct increase in the peak in-cylinder pressure for the methanol-diesel dual-fuel mode. However, the addition of nanoparticles exerted marginal influences on further reduction of CO, HC and smoke emissions, and even further elevated the NOx emissions for MDF mode by up to 40%. Moreover, the deterioration degrees of NOx emissions for alumina and ceria nanoparticle addition were higher than the silica nanoparticles, and elevated towards the higher nanoparticle dosage and lower engine load.